Efektivitas Model Reciprocal Teaching Untuk Meningkatkan Keterampilan Berbicara pada Pembelajaran Bahasa Indonesia - Anni Malihatul Hawa; Lisa Virdinarti Putra; Ela Suryani; Kartika Yuni Purwanti; Hesti Yunitiara Rizqi (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
Lack of students' skills in writing and speaking when learning Indonesian. The reciprocal teaching model is an alternative to increase students' effectiveness in writing and speaking in more optimal Indonesian language learning. The aim of this research is to determine the increase in the effectiveness of Indonesian language learning by implementing the reciprocal teaching model. The research was carried out using a quasi-experimental design with descriptive analysis techniques, normality tests, homogeneity tests and hypothesis tests. The research location was carried out at SD Hj. Isriati Moenadi Ungaran, Semarang with the research sample involving 36 students of class V Imam Bonjol as the experimental class and 36 students of V Kartini as the control class. The average score for speaking skills in Indonesian language learning for experimental class students, which was initially 53.58 after treatment using the reciprocal teaching model, increased to 85.69. The results of the paired sample t test also showed a significance value (Sig.) of 0.001 < 0.05. Based on the results of this research, it proves that there has been an increase in speaking skills in Indonesian language learning, and it can be said that the reciprocal teaching model is effective in improving speaking skills in Indonesian language learning for fifth grade students at Hj Elementary School. Isriati Moenadi Ungaran, Semarang.